CONTROL APPLICATION OF PV SOLAR FARM AS STATCOM FOR INCREASING GRID POWER TRANSFER CAPACITY - PRIYANKA R. YELPALE; DR. H. T. JADHAV; MRS. A. A.CHANDNE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper presents a new control strategy for grid integrated PV solar farm so that it can operate as STATCOM, for improving grid power transmission capacity. Solar farms produce power during day and are completely inactive in nights. The whole ratings of PV Solar Farm, which remain dormant during night, are utilized with voltage and damping control to increase power transmission capacity. The inverter capacity left after the real power production is used to perform above objective. This new control strategy of PV Solar Farm improves power transmission capacity, for which other expensive alternatives are used such as series/shunt capacitor or separate flexible AC transmission system controllers.